Das condições para realização da audiência preliminar obrigatória: uma análise qualitativa das dificuldades enfrentadas na região do agreste meridional de Pernambuco. - Matos, Lucyana Barros Santana de (2021)
The legal hearing of conciliation or mediation, in the initial phase of the process, is mandatory according to the legal provision of article 334 of the Civil Procedure Code of 2015, and challenges the legal community to make it happen and also promote celerity to the deed as the command is observed. The main theme of the research is the analysis of the main difficulties faced in the region of Southern of Pernambuco for the fulfillment of the norm that has provoked different applications by the judges, despite predicting egalitarian application in all the rite processes of the common procedure, with only two exceptions to the waiver, when the law is unavailable or when both parties show a lack on the realization of the act (art. 334, § 4, Civil Procedure Code). A study was achieved on the historical and contemporary aspects of Access to Justice, and a focus on the Multi-Door System in its various modalities, which legitimized the latest procedural reforms, being, the most important, the one that gave birth to the new national civil procedural law. Still in this perspective, the examination of the legislative change of the conciliation or mediation hearing, which went from optional in the previous system, to mandatory in the modern system, and the difficulties in its full implementation, was made. The self-compositional methods in the current expectation lend themselves to solving the demand prematurely, by the parties themselves, without having to go through all the wear and tear of a judicial demand, and consequently, calms the crisis of the judiciary. The research approach is appropriate under the problem, in view of the evidence of non-compliance of the legislation in part of the procedural acquis on the common procedure rite, in the Counties that form the spatial cut, with the waiver of the conciliation hearing or mandatory mediation in the preemial phase. It concludes, proposing, through indicators, the organization of information collected individually in each of the 22 (twenty-two) counties and, through indices, measuring the results of the observational plan, aiming to present them as subsidies for the implementation of institutional actions.